Lucretia and Verginia as virtuous prototypes of femininity in Ancient Rome: stereotypes for a differentiated education - Conesa Navarro, Pedro David (Romanitas - Revista de Estudos Grecolatinos, 2018)
n this paper, we are tring to show the importance that Lucretia and Vergina had for the formation of the gender roles in the Ancient Rome. The deaths of these virtuous women were seen as female prototypes, because the family honor was above private interests. It would not be until the irruption of Christianity when their deaths would be criticized. In addition to reviewing these stories, we will also be interested in the predetermined education that women had, faithful to the domestic sphere as caretakers of the home, mothers and faithful wives.
Keywords: Lucretia; Verginia; Family honor; Roman education